2010
DOI: 10.2747/1539-7216.51.4.437
|View full text |Cite
|
Sign up to set email alerts
|

The Afghanistan-Pakistan Wars, 2008-2009: Micro-geographies, Conflict Diffusion, and Clusters of Violence

Abstract: A team of political geographers analyzes over 5,000 violent events collected from media reports for the Afghanistan and Pakistan conflicts during 2008 and 2009. The violent events are geocoded to precise locations and the authors employ an exploratory spatial data analysis approach to examine the recent dynamics of the wars. By mapping the violence and examining its temporal dimensions, the authors explain its diffusion from traditional foci along the border between the two countries. While violence is still o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 65 publications
1
26
0
Order By: Relevance
“…Although crossnational research has long seen mountainous areas as conducive to insurgent activity (Fearon & Laitin, 2003;Hegre & Sambanis, 2006), disaggregated studies have revealed this relationship to be more complex (O'Loughlin & Witmer, 2011;O'Loughlin et al, 2010;Balcells, 2011). Remote areas may offer ideal conditions for base camps and sanctuaries, but they rarely offer a rich set of targets for attack.…”
Section: Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Although crossnational research has long seen mountainous areas as conducive to insurgent activity (Fearon & Laitin, 2003;Hegre & Sambanis, 2006), disaggregated studies have revealed this relationship to be more complex (O'Loughlin & Witmer, 2011;O'Loughlin et al, 2010;Balcells, 2011). Remote areas may offer ideal conditions for base camps and sanctuaries, but they rarely offer a rich set of targets for attack.…”
Section: Controlmentioning
confidence: 99%
“…The more recent "disaggregated" study of war and insurgency owes much to this older research tradition (O'Loughlin & Witmer, 2011;O'Loughlin et al, 2010;Schutte & Weidmann 2011). However, many applications of geospatial methods to disaggregated conflict data remain descriptive (see review in and most theoretical mechanisms isolated at the macro level -cross-border interactions, alliances and linkage politics -do not travel easily to the micro level, where the propensity of violence to diffuse is more closely tied to military logistics and operational costs (Zhukov, 2012).…”
Section: Insurgency and The Diffusion Of Violencementioning
confidence: 99%
“…At an international (33) and local level (34,35), conflict exhibits qualities that might be described as contagion, diffusion, and clustering patterns. We account for these kinds of dependencies by including a space-time lagged dependent variable.…”
Section: Datamentioning
confidence: 99%
“…body of work on the geography of conflict shows the importance of border regions in conflict diffusion (35). We calculate the mean distance to the border from the centroid of each grid cell.…”
mentioning
confidence: 99%
“…More prominently, the release of confidential documents by the WikiLeaks whistleblower website in July 2010 has provided for the first time a large scale (but uncurated) description of the current Afghan conflict. However, most analyses of these and similar data sources do not go beyond visualization and descriptive statistical methods (2)(3)(4)(5), for good reasons: first, conflict data is highly heterogeneous and often poorly annotated. For example, the WikiLeaks Afghan War Diary (AWD) data used in this study (Dataset S1) consists of event entries as diverse as elaborate preplanned military activity and spontaneous stop-and-search events.…”
mentioning
confidence: 99%